Pembelajaran Matematika Melalui Media Game Quizizz Untuk Meningkatkan Hasil Belajar Siswa - Dermawan, Dwi Ardy; Ramadhan, Alfitrah (ALACRITY : Journal of Education, 2024)
The advancement of science and information and communication technology as one of the products of changing times has had a positive impact on the progress of today's education world. The era of digitalization called the era of the industrial revolution 4.0 made changes very quickly. Many digital learning applications can be used effectively and efficiently as learning support media. This research requires learning media innovation so that students do not feel bored during the teaching and learning process. Many digital learning applications that can be used effectively and efficiently as learning support media The purpose of this research is: to find out the increase in student learning outcomes in the VIIIath Pythagorean theorem material at SMPN 2 Bojonegara. This type of research is Classroom Action Research (CAR). Data collection using the test and observation methods from January to February 2020. The results of this study are; there is an increase in learning outcomes on average learning outcomes 63 in cycle I and 78 in cycle II.